Goat Production in El Salvador: A Focus on Animal Health, Milking Hygiene, and Raw Milk Quality - Kristina Linderot de Cardona; Abelardo De Gracia Scanapieco; Peggy G. Braun (Journal of Food Quality)
Often referred to as “the poor man’s cow,” goats are important livestock in developing countries and in El Salvador goat management and milk are growing in popularity. This study focuses on the general health of Salvadoran goats and national husbandry systems as well as goat products and milking hygiene. The survey was submitted in western and central parts of the country: 191 goat owners were interviewed on animal management and production, 434 goats underwent a basic clinical exam, and raw milk samples were taken from 60 lactating does. Milk samples were examined for total plate count, Staphylococcus aureus, Salmonella spp., Escherichia coli, and Listeria monocytogenes. The majority of goats were managed under a traditional husbandry system naming milk production as their main purpose. Based on the physical exam, the overall goat health was acceptable but in need of improvement. The results of the raw milk samples did not indicate a mayor microbial contamination. Development programs and education of Salvadoran goat owners are recommended to improve goats’ health and productivity in El Salvador. Further studies on the microbial quality on raw goat’s milk are necessary to determine the health risk when consumed. The information obtained in this investigation will serve as a base for future projects.